HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA TANGAN TERHADAP HASIL KETEPATAN POINTING PADA ATLET PETANQUE PROVINSI LAMPUNG - Puput Melati; Lungit Wicaksono; Joan Siswoyo; Dwi Priyono (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
The study aims to identify the flexibility of the wrists and the coordination of the eyes toward the precision of appendists in petanque province of lampung athletes. The method used in this study is corelational. The population in the study was a 20-person petanque provincial lampung athlete and sample technique using a total sampling technique. The data-collection technique used is a survey method using test and measurement based on the flexibility of the wrist by goniometer, whereas eye coordination involves a catch ball test and the precision of the pointing petanque. Research data analysis using product moment correlation analysis. This study suggests that: (1) there is a significant link between the flexibility of the wrist to the precision of the proportionate petanque with a value of rx?.y = 0,658> r(0,05)(18)= 0,468 (2) there is a significant link between hand eye coordination of the precision of certain petanque with a value of rx?.y= 0,657> r(0,05)(18)= 0,468 (3) there is a significant connection between the elasticity of the wrist and coordination eye hand the precision of the proportionate petanque with a value of rx?.x?.y= 0,924 > r(0,05)(18)= 0,468. Thus it can be concluded that there was a significant connection between the flexibility of the wrist and the coordination of the eye toward the precision of appendization in the jokers of the subordinate province of petanque.